Εθνογραφικό, ανθρωπολογικό ντοκιμαντέρ: η οπτική αφήγηση της πραγματικότητας - Παναγιώτου, Μαρίνος (Department of Communication and Internet Studies, Faculty of Communication and Media Studies, Cyprus University of Technology, 2017)
The core outcome of the course “Dissertation” is the film itself, while the present document clarifies the academic research that was conducted before, during and after the production of the documentary. The aim of the film is to speak for a social phenomenon, the phenomenon of migration, by using the language of visual communication. Through the recording of a local story, the aim is to reveal the international dimension of migration. The methodology that was used is split into three stages, the developmental stage, the pre-production stage, and the post-production stage. The procedures followed in each stage are presented thoroughly in each methodology chapter. The movie records the life of two people who cohabitate and continue to live under different circumstances, facing the consequences of migration. Mrs Kornelia, 107 year old and a mother of five daughters, of which 4 have migrated abroad at their early adulthood years and now live permanently in Australia, and Ms Mayia, who is from Nepal, but has migrated herself to Cyprus to work as the domestic assistant of Mrs. Kornelia. Ms Mayia, is the mother of 2 adult children, who continue to live back in their home country. The two ladies live together at Mrs Kornelia house in Agios Demitrianos village in Paphos for the past 2 years and continue to do so at the time of writing this report. The camera records the behaviors, emotions and habits of the old lady as well as the ones of the domestic assistant, that express the meaning of migration, the circumstances and reasons that led to it.
Keywords: Documentary; Anthropology; Ethnography; Short film; Migration; Ντοκιμαντέρ; Ανθρωπολογία; Εθνογραφία; Μετανάστευση; Ταινίες μικρού μήκους